In vitro and in vivo comparison of a tailored magnetic particle imaging blood pool tracer with Resovist. (5th April 2017) - Kaul, Michael Gerhard; Mummert, Tobias; Jung, Caroline; Salamon, Johannes; Khandhar, Amit P; Ferguson, R Matthew; Kemp, Scott J; Ittrich, Harald; Krishnan, Kannan M; Adam, Gerhard; Knopp, Tobias
Abstract: Optimizing tracers for individual imaging techniques is an active field of research. The purpose of this study was to perform in vitro and in vivo magnetic particle imaging (MPI) measurements using a new monodisperse and size-optimized tracer, LS-008, and to compare it with the performance of Resovist, the standard MPI tracer. Magnetic particle spectroscopy (MPS) and i n vitro MPI measurements were performed in concerns of concentration and amount of tracer in a phantom. In vivo studies were carried out in healthy FVB mice. The first group ( n = 3) received 60 µ l LS-008 (87 mM) and the second ( n = 3) diluted Resovist of the same concentration and volume. Tracer injections were performed with a syringe pump during a dynamic MPI scan. For anatomic referencing MRI was applied beforehand of the MPI measurements. Summing up MPS examinations and in vitro MPI experiments, LS-008 showed better sensitivity and spatial resolution than Resovist. In vivo both tracers can visualize the propagation of the bolus through the inferior vena cava. MPI with LS-008 did show less temporal fluctuation artifacts and the pulsation of blood due to respiratory and cardiac cycle was detectable. With LS-008 the aorta was distinguishable from the caval vein while with Resovist this failed. A liver vessel and a vessel structure leading cranially could only be observed with LS-008 and not with Resovist. Beside these structural advantages both tracers showed very different blood half-life. For LS-008 we found 88 min. Resovist did show a fast liver accumulation and a half-life of 13 min. Only with LS-008 the perfusion fraction in liver and kidney was measureable. MPI for angiography can be significantly improved by applying more effective tracers. LS-008 shows a clear improvement concerning the delineation while resolving a larger number of vessels in comparison to Resovist. Therefore, in aspects of quality and quantity LS-008 is clearly favorable for angiographic and perfusion studies.